Transient aggregates in protein folding are easily mistaken for folding intermediates - Silow, Maria (The National Academy of Sciences of the USA, 1997)
It has been questioned recently whether populated intermediates are important for the protein folding process or are artefacts trapped in nonproductive pathways. We report here that the rapidly formed intermediate of the spliceosomal protein U1A is an off-pathway artefact caused by transient aggregation of denatured protein under native conditions. Transient aggregates are easily mistaken for structured monomers and could be a general problem in time-resolved folding studies.